Setting up of teeth in the neutral zone and its effect on speech - Wafa’a Radwan Al-Magaleh; Amal Ali Swelem; Sahar Saad Shohdi; Nadia Mohamed Mawsouf (Saudi Dental Journal)
Rational goals for denture construction are basically directed at the restoration of esthetics and masticatory function and the healthy preservation of the remaining natural tissues. Little concern has been given to the perfection and optimization of the phonetic quality of denture users. However, insertion of prosthodontic restorations may lead to speech defects. Most such defects are mild but, nevertheless, can be a source of concern to the patient. For the dental practitioner, there are few guidelines for designing a prosthetic restoration with maximum phonetic success. One of these guidelines involves the setting up of teeth within the neutral zone. The aim of this study was to evaluate, subjectively and objectively, the effect on speech of setting up teeth in the neutral zone. Three groups were examined: group I (control) included 10 completely dentulous subjects, group II included 10 completely edentulous patients with conventional dentures, and group III included the same 10 edentulous patients with neutral zone dentures. Subjective assessment included patient satisfaction. Objective assessment included duration taken for recitation of Al-Fateha and acoustic analysis. Subjectively, patients were more satisfied with their neutral zone dentures. Objectively, speech produced with the neutral zone dentures was closer to normal than speech with conventional dentures. Keywords: Neutral zone, Speech, Complete dentures, Patient satisfaction, Consonants, Vowels